2008
DOI: 10.1016/j.psychres.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of suicidal and self-injurious behavior among subjects with intermittent explosive disorder

Abstract: The prevalence of suicidal attempts and self-injurious behavior among 376 patients diagnosed with Intermittent Explosive Disorder (IED) was assessed via structured interviews. Results showed 16% of IED subjects reported self-aggression, with 12.5% reporting suicide attempts and 7.4% reporting non lethal self-injurious behaviors. Additional risk factors were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 9 publications
(10 reference statements)
1
19
0
1
Order By: Relevance
“…Trait aggression is linked with the tendency to engage in NSSI (Haavisto et al, 2005; Hillbrand, Krystal, Sharpe, & Foster, 1994; Tang et al, 2013). At clinical levels, aggression is a component of intermittent explosive disorder, which is associated with increased prevalence of NSSI (McCloskey, Ben-Zeev, Lee, & Coccaro, 2008). In adolescents, aggression is found to be a distal predictor of NSSI, which is mediated by emotion regulation (Adrian, Zeman, Erdley, Lisa, & Sim, 2010).…”
mentioning
confidence: 99%
“…Trait aggression is linked with the tendency to engage in NSSI (Haavisto et al, 2005; Hillbrand, Krystal, Sharpe, & Foster, 1994; Tang et al, 2013). At clinical levels, aggression is a component of intermittent explosive disorder, which is associated with increased prevalence of NSSI (McCloskey, Ben-Zeev, Lee, & Coccaro, 2008). In adolescents, aggression is found to be a distal predictor of NSSI, which is mediated by emotion regulation (Adrian, Zeman, Erdley, Lisa, & Sim, 2010).…”
mentioning
confidence: 99%
“…Adolescents and young adults may experience educational and social consequences but also mental health problems,4 including parasuicide,13 if IED/EDS is undiagnosed in early childhood. Consequently, earlier recognition and treatment of IED/EDS could potentially prevent these complications, with obvious benefits for the individual and their community.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is intermittent in nature, the association with modest impairment in the work domain was not surprising. Nonetheless, IED might be associated with violent behaviors (30). Thus, its overall impairment was comparable to that of chronic physical disorders (4,5).…”
Section: S Lee Et Almentioning
confidence: 97%
“…It is characterized by recurrent episodes of serious assaultive acts that are out of proportion to psychosocial stressors (29,30). Recent studies found that IED is far more common than previously thought (29) and was the third most common 12-month disorder in Beijing and Shanghai (16).…”
Section: S Lee Et Almentioning
confidence: 99%